2005
DOI: 10.1105/tpc.105.032714
|View full text |Cite
|
Sign up to set email alerts
|

Seven Lotus japonicus Genes Required for Transcriptional Reprogramming of the Root during Fungal and Bacterial Symbiosis

Abstract: A combined genetic and transcriptome analysis was performed to study the molecular basis of the arbuscular mycorrhiza (AM) symbiosis. By testing the AM phenotype of nodulation-impaired mutants and complementation analysis, we defined seven Lotus japonicus common symbiosis genes (SYMRK, CASTOR, POLLUX, SYM3, SYM6, SYM15, and SYM24) that are required for both fungal and bacterial entry into root epidermal or cortical cells. To describe the phenotype of these mutants at the molecular level, we screened for differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
286
0
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(306 citation statements)
references
References 73 publications
(117 reference statements)
7
286
0
9
Order By: Relevance
“…Unlike LNP, the SYM pathway is not necessary for the Nod factorinduced calcium influx response (Miwa et al, 2006a), although it has been reported that M. truncatula mutated in dmi1 or dmi2 cannot support the complete calcium influx response (Shaw and Long, 2003). Furthermore, analysis in L. japonicus mutants of SYM pathway components identified various steps of mycorrhizal colonization of roots (Novero et al, 2002;Demchenko et al, 2004;Kistner et al, 2005). In all the early L. japonicus mutants defective for arbuscular mycorrhization identified so far, fungal hyphae have been observed to enter between epidermal cells, but the intracellular penetration of epidermal or outer cell layers is blocked except in Ljsym15, in which mycorrhization is blocked at the separation of anticlinal walls of epidermal cells and arbuscule formation (Demchenko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike LNP, the SYM pathway is not necessary for the Nod factorinduced calcium influx response (Miwa et al, 2006a), although it has been reported that M. truncatula mutated in dmi1 or dmi2 cannot support the complete calcium influx response (Shaw and Long, 2003). Furthermore, analysis in L. japonicus mutants of SYM pathway components identified various steps of mycorrhizal colonization of roots (Novero et al, 2002;Demchenko et al, 2004;Kistner et al, 2005). In all the early L. japonicus mutants defective for arbuscular mycorrhization identified so far, fungal hyphae have been observed to enter between epidermal cells, but the intracellular penetration of epidermal or outer cell layers is blocked except in Ljsym15, in which mycorrhization is blocked at the separation of anticlinal walls of epidermal cells and arbuscule formation (Demchenko et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In all the early L. japonicus mutants defective for arbuscular mycorrhization identified so far, fungal hyphae have been observed to enter between epidermal cells, but the intracellular penetration of epidermal or outer cell layers is blocked except in Ljsym15, in which mycorrhization is blocked at the separation of anticlinal walls of epidermal cells and arbuscule formation (Demchenko et al, 2004). In the LjsymRK mutant, fungal hyphae form appressoria and balloon-like deformations, but the subsequent fungal entry in cells of epidermis and exodermis was aborted, blocking the intracellular passage (Demchenko et al, 2004;Kistner et al, 2005). Attachment of fungal hyphae and appressorium formation were observed on the root surface of three LNP antisense lines, but intercellular or intracellular entry in the epidermal cells was not observed, implying a role for LNP in events leading to the epidermal cell entry of fungal hyphae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is indeed the case: sli-1 was isolated as a negative regulator of the EGFR signaling pathway in the nematode, and it was discovered that sli-1 encoded a homolog of c-CBL, a putative oncogene whose function had not been revealed at that time Yoon et al, 1995). As soon as the identity of sli-1 was published, the mammalian CBL proteins became intensively researched and soon much was known about these proteins in terms of their biochemical functions and their roles in the signaling pathway (for example, Bowtell and Langdon, 1995;Galisteo et al, 1995;Lupher et al, 1996;Hime et al, 1997;Meisner et al, 1997;Miyake et al, 1997;Smit and Borst, 1997;Lupher et al, 1998;Broome et al, 1999). Another gene, ark-1, was also identified as a component of the EGFR signaling pathway in the nematode vulval development, and it was determined to be an ACK-related kinase (Hopper et al, 2000).…”
Section: Nematode As a Model System For Oncogene Studiesmentioning
confidence: 99%
“…For example, SymRK, the receptor-like kinase gene, is required for both rhizobial and AM symbioses (Stracke et al, 2002). Similarly, the signal transduction pathways following perception are also in part the same, and the genes common to the two pathways have been referred to as the common symbiosis (SYM) genes (Kistner et al, 2005). These similarities may reflect common mechanisms for host plant cells to respond to symbionts, although the commonality is not globally defined yet.…”
mentioning
confidence: 99%